2018
DOI: 10.1016/j.ejon.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomised controlled trial of a multimodal supportive care (ThriverCare) intervention for managing unmet supportive care needs in men with metastatic prostate cancer on hormonal treatment and their partner/caregivers

Abstract: A pilot randomised controlled trial of a multimodal supportive care (ThriverCare) intervention for managing unmet supportive care needs in men with metastatic prostate cancer on hormonal treatment and their partner/caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(77 citation statements)
references
References 36 publications
1
75
0
1
Order By: Relevance
“…Of the 13 studies included in our review, nine are RCTs and four are quasi‐experimental studies 35 . Six studies were conducted in the United States, 36–40 while the remaining studies were conducted in Sweden, 41 Northern Ireland, 42 the Netherlands, 43 United Kingdom, 44 Malaysia, 45 Iran 46 and Norway 47 . All studies included were published between 2007 and 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 13 studies included in our review, nine are RCTs and four are quasi‐experimental studies 35 . Six studies were conducted in the United States, 36–40 while the remaining studies were conducted in Sweden, 41 Northern Ireland, 42 the Netherlands, 43 United Kingdom, 44 Malaysia, 45 Iran 46 and Norway 47 . All studies included were published between 2007 and 2019.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of the studies ranged considerably, with the RCTs ranging from 16 37 to 179 47 participants, and the quasi‐experimental studies ranging from 38 40 to 105 46 . Eleven studies focused specifically on older adults, 36,39–48 whereas two studies conducted a subgroup analysis 37,38 . A summary of the characteristics of each study included in this systematic review can be found in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Ruesch et al 4 emphasized the need for a sensitive, individual, and needs‐oriented approach to informing patients and partners. Paterson et al 32 and McCabe et al 17 noted that a one size fits all care approach is not applicable, and care should be customized to the unique needs of an individual. Our findings underscore the conclusions of the authors by indicating that the provision of information must be responsive to individual needs and should be adapted accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that caregivers play an important role in the rehabilitation process of patients (Kemp et al., 2018). Moreover, many interventions for patient–caregiver dyads have attempted to improve both caregivers’ and patients’ health (Paterson, Primeau, & Nabi, 2018; Stockwell‐Smith, Moyle, & Kellett, 2018).…”
Section: Introductionmentioning
confidence: 99%